Como enfrentar os obstáculos frequentes em éguas portadores de alterações genitais passíveis de tratamento cirúrgico - Prestes, Nereu Carlos [UNESP]; Lourenção, Josiane Adelaine Camargo [UNESP] (My University, 2015)
In order to face the challenges of surgical act, reading Jürgen Thorwald's book “The Century of the Surgeon” (Das Jahrhundert der Chirurgen) is a must. In his book, the author describes the beginning of surgical procedures before and after the discovery of anaesthetic drugs, the bloody techniques used in those times, the amputations, the caesarean section, the evidence of bacterial contamination, and the principles of antisepsis (Thorwald, 2010). The difficulties and improvisations faced by the pioneers in equine medicine are historically reported in the book “ArsVeterinaria”, carefully reported by Walker (1991), who tells about the importance of horses in human history and about the use of those animals for transportation, leisure and military purposes, specially on great battles involving explorers and the Greek-Roman empire, including illustrations of the handmade surgical instruments used in that time. The aim of this text is to present a summary of the main obstacles faced in mares reproductive surgery, with no pretension to exhaust the subject, but to report part of the personal experience of this professional, grounded in specialized literature.

Para entender a enfrentar os desafios do ato cirúrgico torna-se necessário a leitura obrigatória do livro “O século dos cirurgiões”, onde o autor descreveu os primórdios dos procedimentos antes e após o advento e descoberta das drogas anestésicas, as técnicas cruentas utilizadas na época, as amputações, a operação cesariana, a comprovação da contaminação bacteriana e os princípios da antissepsia (Thorwald, 2010). As dificuldades em improvisações enfrentadas pelos praticantes pioneiros da medicina veterinária equina estão historicamente relatadas no livro “Ars Veterinária” detalhadamente compiladas por Walker (1991), onde escreveu uma narrativa da importância do cavalo na história do ser humano e sua utilização como meio de transporte, lazer e atividade militar nas grandes batalhas principalmente dos exploradores e dos impérios greco-romano, contendo ilustrações do instrumental cirúrgico artesanal utilizado na época. O objetivo desse texto será o de apresentar uma súmula dos principais obstáculos enfrentados nas cirurgias do trato reprodutivo das éguas sem a pretensão de esgotar o assunto, mas sim deixar registrado uma parte da experiência pessoal deste profissional embasado na literatura especializada.
Facing the most frequent challenges in mares with genital alterations that may be corrected by surgery
Keywords: Challenge; Mares; Reproductive tract; Surgery; Cirurgias; Desafios; Éguas; Trato reprodutivo